The Princippal's Prophetic Leadership in Improving Teacher’s Performance - Nafi'a, Ilman; Gumiandari, Septi (IAIN Syekh Nurjati Cirebon, 2022)
The performance of the principal can be a role modeling for the performance of the teachers. If an educational institution is managed with the prophetic leadership ability of the principal, the managerial system will be able to foster responsibility that comes from the hearts and internal motivations of teachers. This study aims to describe the Prophetic Leadership of The Principal in Improving Teacher Performance. This research uses a literature reviews approach. In searching for articles, a google scholar application is used with the keywords